L’oralité fantasmée de l’histoire - Léo Stambul (Cahiers d’Études Romanes, 2023)
When the French army under the command of Louis XIV crossed the Rhine in 1672, many historians tried to record the event as collective memory with various endeavours to celebrate the King: newspapers, poems, or medals. Despite the absence of precise testimony, each author invented a fictitious form of orality supposedly produced and recorded on the spot and in awe. Comparing the ways orality was resorted to helps questioning the fantasy which pervades the different modalities to write history in the context of absolute monarchy.